2020
DOI: 10.1038/s41598-020-58690-4
|View full text |Cite
|
Sign up to set email alerts
|

Rifampicin Resistant Tuberculosis in Lesotho: Diagnosis, Treatment Initiation and Outcomes

Abstract: the Lesotho guidelines for the management of drug-resistant tuberculosis (tB) recommend initiation of patients diagnosed with rifampicin resistant (RR)-tB on a standardized drug resistant regimen while awaiting confirmation of rifampicin resistant TB (RR-TB) and complete drug susceptibility test results. Review of diagnostic records between 2014 and 2016 identified 518 patients with RR-TB. Only 314 (60.6%) patients could be linked to treatment records at the Lesotho MDR hospital. The median delay in treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 11 publications
0
11
2
4
Order By: Relevance
“…A multi-centre study conducted in South Africa and Uganda reported a linkage to care rate of 55% (12/22) amongst HIV-positive patients diagnosed with active drug-susceptible TB, while a study in Malawi reported a linkage to care rate of 40% (23/58) amongst hospitalized patients diagnosed with TB in Lilongwe ( Chawla et al., 2016 ; Shapiro et al., 2018 ). In Lesotho, a study assessing treatment initiation of patients diagnosed with rifampicin-resistant TB using the GeneXpert assay reported a linkage to care rate of 60.6% (314/528) ( Katende et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multi-centre study conducted in South Africa and Uganda reported a linkage to care rate of 55% (12/22) amongst HIV-positive patients diagnosed with active drug-susceptible TB, while a study in Malawi reported a linkage to care rate of 40% (23/58) amongst hospitalized patients diagnosed with TB in Lilongwe ( Chawla et al., 2016 ; Shapiro et al., 2018 ). In Lesotho, a study assessing treatment initiation of patients diagnosed with rifampicin-resistant TB using the GeneXpert assay reported a linkage to care rate of 60.6% (314/528) ( Katende et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study analysing the Lesotho TB diagnostic network reported a national linkage to care rate of 82%, with 2806 of the 3435 patients diagnosed with TB in 2016 initiated on treatment; the remaining 18% of patients could not be traced ( Albert et al., 2020 ). Another study assessing the impact of GeneXpert implementation on the diagnosis, treatment initiation and treatment outcomes of patients with rifampicin-resistant TB reported a linkage to care rate of 61% amongst patients diagnosed between 2014 and 2016; it is likely that the remaining 39% of patients never initiated drug-resistant treatment ( Katende et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in treatment initiation is similar to what was observed in a nationwide retrospective cohort study in Johannesburg, South Africa, which was reported in 2011 and 2013, when GeneXpert MTB/RIF was implemented across districts and provinces. The results showed that the proportion of patients in whom appropriate TB resistance treatment was initiated increased from 6% to 19% [ 37 ]. Some studies found that the usage of GeneXpert MTB/RIF among patients at risk of drug-resistant TB was low [ 38 – 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Drug susceptibility tests were performed by laboratory technologists from the TB laboratory using a fully automated Mycobacterial Growth Indicator Tube (MGIT) 960 liquid culture system (Becton Dickinson, USA). The critical concentrations of anti-TB drugs in these specific assays were as follows: rifampicin, 1.0 μg/ml (MGIT); isoniazid, 0.1 μg/ml (MGIT); ethambutol, 5.0 μg/ml (MGIT); streptomycin, 1.0 μg/ml (MGIT); ofloxacin, 1.5 μg/ ml (MGIT); capreomycin, 2.5 μg/ml (MGIT); and amikacin, 1.0 μg/ml (MGIT) [7]. All experimental methods conformed to standardised clinical laboratory procedures and operating regulations.…”
Section: Sample Collection and Processingmentioning
confidence: 99%